Neoadjuvant chemotherapy or primary debulking surgery in FIGO IIIC and IV patients; results from a survey study in the Netherlands. (April 2018) - Timmermans, M.; Sonke, G.S.; van Driel, W.J.; Lalisang, R.I.; Ottevanger, P.B.; de Kroon, C.D.; Van de Vijver, K.K.; van der Aa, M.A.; Kruitwagen, R.F.
Abstract: Introduction: Primary debulking surgery (PDS) followed by adjuvant chemotherapy is historically recommended as first line treatment for advanced stage ovarian cancer. Two randomized controlled trials, however, showed similar efficacy and reduced toxicity with neoadjuvant chemotherapy followed by interval debulking surgery (NACT-IDS). Nevertheless, uptake of NACT-IDS varies widely between hospitals, which cannot be explained by difference in patient populations. In this survey, we therefore aimed to evaluate the views on NACT-IDS among all Dutch gynaecologists and medical oncologists involved in the treatment of ovarian cancer. Study design: An e-mail link to the online questionnaire was sent to all medical oncologists and gynaecologists in the Netherlands, regardless of their (sub)specializations. The data was analysed using descriptive statistics and chi-square tests were used to analyse differences between groups. Results: Three-hundred-forty physicians were invited to fill out the questionnaire. After two reminders, 167 of them responded (49%). Among the responders, 82% of the gynaecologists versus 93% of the medical oncologists considered the available evidence sufficiently convincing to treat advanced stage ovarian cancer patients with NACT-IDS (p = 0.076). Moreover, 33% of gynaecologists and 62% of medical oncologists preferred NACT-IDS to PDS as first line treatment (p = 0.001). While most responders (86%) indicated that selecting the right patients for NACT-IDS is difficult, those with bulky disease, FIGO stage IV or metastases near the porta hepatica were most likely to undergo NACT-IDS. Conclusion: The majority of Dutch gynaecologists and medical oncologists adopted NACT-IDS as an alternative treatment approach for advanced stage primary ovarian cancer. About two-thirds of medical oncologists and one-third of gynaecologists prefer NACT-IDS to PDS as first line treatment in this setting. Improving patient selection is considered of paramount importance.